2022
DOI: 10.1186/s13613-022-00981-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of ventilator type with hospital mortality in critically ill patients with SARS-CoV2 infection: a prospective study

Abstract: Background To evaluate the association between ventilator type and hospital mortality in patients with acute respiratory distress syndrome (ARDS) related to COVID-19 (SARS-CoV2 infection), a single-center prospective observational study in France. Results We prospectively included consecutive adults admitted to the intensive care unit (ICU) of a university-affiliated tertiary hospital for ARDS related to proven COVID-19, between March 2020 and July… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
7
1
1
Order By: Relevance
“…The surge in patients with COVID-19 requiring hospitalization, ICU admission, and ventilator support has posed an unparalleled challenge to physicians, nurses, hospital managers, and healthcare systems. Due to the limitation and shortage of critical care equipment in ICUs, a considerable proportion of patients who need MV are treated with transport ventilators in hospital settings outside the ICU 10 , 17 . However, despite the widespread use of transport ventilators in medical centers, their impact on COVID-19 patients' outcomes is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surge in patients with COVID-19 requiring hospitalization, ICU admission, and ventilator support has posed an unparalleled challenge to physicians, nurses, hospital managers, and healthcare systems. Due to the limitation and shortage of critical care equipment in ICUs, a considerable proportion of patients who need MV are treated with transport ventilators in hospital settings outside the ICU 10 , 17 . However, despite the widespread use of transport ventilators in medical centers, their impact on COVID-19 patients' outcomes is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center prospective observational study by Ferre et al 17 , evaluated the association between ventilator type and hospital mortality in patients with ARDS related to COVID-19. They demonstrated that management in a transient ICU equipped with non-ICU sophisticated turbine-based ventilators was not associated with worse outcomes compared to a standard ICU equipped with ICU ventilators.…”
Section: Introductionmentioning
confidence: 99%
“…Second, ventilator availability in both ICUs differed. Ferré et al used a transport ventilator without identifying consequences regarding the outcome [ 15 ]. Because of the lack of intensive care specialized ventilators at the beginning of the crisis, the temporary ICU in our department was equipped with either older model or anaesthesia ventilators.…”
Section: Discussionmentioning
confidence: 99%
“…The online supplementary e-Figure 1 shows the monthly incidence of ICU case fatality rates throughout the pandemic between waves. The results showed a significant difference in ICU length of stay regarding the COVID wave as follows: 20 [IQR: in W1 versus 14 [IQR: [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] days in W2 and 12 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] days in W3, p = 0.001. The results on survival rates did not show significant differences in ICU, hospital, or day-90 survival for patients according to the wave (Table 2).…”
Section: Comparison According To the Epidemic Wavesmentioning
confidence: 99%
“…During the first wave, intensivists have faced a new severe pulmonary infectious disease with high homogeneity in patient characteristics according to published studies. Pulmonary patterns were mild to severe acute respiratory distress syndrome (ARDS) requiring invasive mechanical ventilation (MV) as a cornerstone of symptomatic ICU management at this time [5][6][7][8][9][10]. From January to June 2020, no treatment has proven to be effective, and international guidelines recommended symptomatic ICU management and/or therapeutic options only in the context of randomized controlled studies [11,12].…”
Section: Introductionmentioning
confidence: 99%